Georgij Efron: Tagebücher. Band II. (1941-43) - Hollitzer Verlag (Hollitzer, 2022)
The Diaries, Volume II, continue after the death of Marina Tsvetaeva, he returns to Moscow, where he could stay with aunt Lilja, a sister of his father, living off from selling items that he inherited from his mother. At that time Moscow was undergoing air raids; the situation was devastating and became more and more chaotic. He feared to get drafted for work at the defense wall. So, he decided to join a transport of the Union of Soviet Writers to Uzbekistan. The Diaries of Georgij Ėfron may be considered a singular historical document, nobody dared to put down in writing freely and uncensured unorthodox thoughts and commentaries about the deplorable and miserable condition of the Soviet society and the hardship of a life as an evacuee in the hinterlands. His notes are of an astonishing high literary quality as well. Volume 1: http://e-book.fwf.ac.at/o:1775 Volume 2: http://e-book.fwf.ac.at/o:1776 Die Tagebücher, Band II, setzen nach dem Tod von Marina Cvetaeva fort, Georgij Sergeevič Ėfron kommt vorerst in das Kinderheim in Čistopol’, kehrt aber bald nach Moskau zurück, wo er bei einer Tante väterlicherseits unterkommt. Er lebt vom Erbe seiner Mutter und beschreibt, was sich in Moskau abspielt, wo die Belagerung durch den Feind bevorstehen könnte, er muss damit rechnen, eingezogen zu werden und schließt sich einem Evakuierungstransport des Schriftstellerverbandes an, der Taškent, Uzbekische SSR, zum Zielort hat. Die Tagebücher von Georgij Sergeevič Ėfron sind nicht nur von erstaunlicher literarischer Qualität, sondern auch ein singuläres historisches Zeugnis, niemand sonst wagte es zur damaligen Zeit in der Sowjetunion, so frei und unbekümmert seine Überlegungen und Gedanken zu den gesellschaftlichen Gegebenheiten niederzuschreiben. Band 1: http://e-book.fwf.ac.at/o:1775 Band 2: http://e-book.fwf.ac.at/o:1776
Keywords: Sowjetunion; Russland; Frankreich; Mokau; Paris; Jelabuga; Stalin; Hitler; Lyrik; Zwetajewa; 2. Weltkrieg; Ã FOS 2012 – GEISTESWISSENSCHAFTEN (6) – Sprach- und Literaturwissenschaften (602) – Sprach- und Literaturwissenschaften (6020) – Slawistik (602047); Ã FOS 2012 – GEISTESWISSENSCHAFTEN (6) – Geschichte; Archäologie (601) – Geschichte; Archäologie (6010) – Zeitgeschichte (601022); Ã FOS 2012 – SOZIALWISSENSCHAFTEN (5) – Soziologie (504) – Soziologie (5040) – Jugendsoziologie (504016); Ã FOS 2012 – GEISTESWISSENSCHAFTEN (6) – Sprach- und Literaturwissenschaften (602) – Sprach- und Literaturwissenschaften (6020) – Romanistik (602042); Soviet Union; Russia; France; Moscow; Paris; Jelabuga; Stalin; Hitler; Poetry; Tsvetaeva; World War II; Ã FOS 2012 – HUMANITIES (6) – Linguistics and Literature (602) – Linguistics and Literature (6020) – Slavonic studies (602047); Ã FOS 2012 – HUMANITIES (6) – History; Archaeology (601) – History; Archaeology (6010) – Contemporary history (601022); Ã FOS 2012 – SOCIAL SCIENCES (5) – Sociology (504) – Sociology (5040) – Sociology of youth (504016); Ã FOS 2012 – HUMANITIES (6) – Linguistics and Literature (602) – Linguistics and Literature (6020) – Romance studies (602042); Diaries